2000
DOI: 10.1103/physrevlett.84.5963
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Spin-FlipM1 Transition inLΛ7i

Abstract: Using a large-acceptance germanium detector array (Hyperball), we have observed a spin-flip M1 gamma transition between the ground-state spin doublet of (7)(Lambda)Li (3/2(+)-->1/2(+)). The observed energy of 691.7+/-0.6(stat)+/-1.0(syst) keV provides crucial information on the strength of the spin-spin interaction between a Lambda and a nucleon. This is the first observation of well-identified hypernuclear gamma transitions using germanium detectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(78 citation statements)
references
References 18 publications
1
77
0
Order By: Relevance
“…The other purpose is to cross-check the ΛN spin-dependent interaction parameters which have been determined from the 7 Λ Li, 9 Λ Be, and 16 Λ O experiments with Hyperball. The experimental setup is almost identical to the one in E419 [1,5]. We used a 10 cm-thick 98%-enriched 11 B metal target.…”
Section: Spectroscopy Of 11 λ B (E518)mentioning
confidence: 99%
See 1 more Smart Citation
“…The other purpose is to cross-check the ΛN spin-dependent interaction parameters which have been determined from the 7 Λ Li, 9 Λ Be, and 16 Λ O experiments with Hyperball. The experimental setup is almost identical to the one in E419 [1,5]. We used a 10 cm-thick 98%-enriched 11 B metal target.…”
Section: Spectroscopy Of 11 λ B (E518)mentioning
confidence: 99%
“…Together with the E419 results [1], we have clarified the complete level scheme and energies of all the bound states of 7 Λ Li as shown in Fig. 1 (a).…”
Section: Complete Study Ofmentioning
confidence: 99%
“…An experimental technique to use Germanium (Ge) detectors with a high energy resolution is necessary to resolve energy splitting of non-zero spin states of a core-nucleus. Since 1998, γ rays 1 [1][2][3][4][5][6][7][8][9]. These results are a good bench mark of ΛN interaction and Λ-hypernuclei.…”
Section: Introductionmentioning
confidence: 59%
“…In p-shell Λ hypernuclei, experimental and theoretical studies have revealed a couple of interesting structure changes. For example, the reduction of the intercluster distance by the Λ hyperon in s-orbit has been confirmed through the observation of E2 transition probabilities B(E2) in 7 Λ Li [1,2,3,4], that has the developed α + d + Λ cluster structure. In sd-shell Λ hypernuclei, various structure changes have been predicted theoretically, because normal sd-shell nuclei have a variety of structures, such as cluster structure and mean-field like structure with axial/triaxial deformation, in the ground and low-lying states.…”
Section: Introductionmentioning
confidence: 88%